1991
DOI: 10.1093/carcin/12.8.1417
|View full text |Cite
|
Sign up to set email alerts
|

Presence of carcinogenic heterocyclic amines in urine of healthy volunteers eating normal diet, but not of inpatients receiving parenteral alimentation

Abstract: For estimation of human exposures to carcinogenic heterocyclic amines, the amounts of four compounds, 3-amino-1, 4-dimethyl-5H-pyrido[4,3-b]indole (Trp-P-1), 3-amino-1-methyl-5H-pyrido[4,3-b]indole (Trp-P-2), 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) and 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx), in human urine were measured. Twenty-four hour urine specimens were collected from ten healthy volunteers eating normal diet (five males and five females) and three inpatients (two males and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(87 citation statements)
references
References 0 publications
5
80
0
2
Order By: Relevance
“…The level of APNH in human urine samples was much lower than found earlier for MeIQx, but comparable with that for 3-amino-1,4-dimethyl-5H-pyrido [4,3-b]indole (Trp-P-1; ref. 13). However, APNH is a more potent carcinogen than Trp-P-1 and MeIQx (10,28), so that the risk of human cancer might be similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of APNH in human urine samples was much lower than found earlier for MeIQx, but comparable with that for 3-amino-1,4-dimethyl-5H-pyrido [4,3-b]indole (Trp-P-1; ref. 13). However, APNH is a more potent carcinogen than Trp-P-1 and MeIQx (10,28), so that the risk of human cancer might be similar.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 H 4 ]APNH was used as an internal standard and added to each urine sample before blue rayon treatment. The urine sample was treated with 6 g blue rayon for three times, which was then washed with water, and adsorbed materials were extracted with 1.2 liters of methanol/ammonia water (50:1, v/v), as previously reported (13). The extracts were evaporated to dryness, and the residues were dissolved in methanol and further purified by high-performance liquid chromatography (HPLC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the cooking process, pyrolysis of meat liquids can result in the formation of mutagenic and carcinogenic heterocyclic amines (14), such as 2-amino-3-methylimidazo[4,5-J]quinoline (IQ), 2-amino-3,8-dimethylimidazo-[4,5-flquinoxaline (MeIQx), 2-amino-1-methyl-6-phenyHmidazo [4,5-b]pyridine (PhIP), and 2-amino-6-methyldipyrido[1,2-a:3',2'-d]imidazole (Glu-P-1). Several of these aromatic amines are known to induce tumors in experimental animals in a variety of tissues, notably the liver and intestine (15); and they have also been detected in urine of individuals who consume a normal, meat-containing diet (16). Their metabolic activation pathways have been extensively studied in rodents, and we have recently shown that human liver and colon tissues possess comparable enzyme systems (17).…”
Section: Introductionmentioning
confidence: 99%
“…The positive correlation between meat consumption and cancer incidence such as those of the stomach (5), prostate (6), breast (7,8), lung (9) in human populations (10) along with carcinogenicity to rats and mice (11)(12)(13) of these compounds suggest that they may be an important factor in diet-related human cancers. The critical step in HCA bioactivation is catalyzed by the CYP mediated A/-hydroxylation, forming its major metabolite, A/-hydroxy HCA (14)(15)(16)(17). The presence of CYP1A2, CYP1A1 and CYP1B1 mRNA in the human prostate has been reported (18).…”
mentioning
confidence: 99%